Analsis Implementasi Kebijakan Pemungutan Pajak Reklame Videotron Dalam Rangka Peningkatan Penerimaan Pajak Reklame Pada Unit Pelayanan Pemungutan Pajak Daerah Wilayah Menteng Jakarta Pusat Tahun 2021 - Muhamad Ridwan Rinaldi; Rahadi Pratomo Singgih (Jurnal Ilmu Administrasi Publik, 2023)
Advertisement   tax   has   become   an   interesting   topic   for   study. Advertisements are widely used by various institutions, both business and non-business, to convey specific information. The development of businesses accompanied by rapid technological advancements makes the development  of advertisements worth noting, especially  from a taxation perspective which may be a promising source of revenue for local  governments.  One  form  of  advertisement  that  is  currently developing is the videotron type. Videotron is an electronic medium that displays videos using Light Emitting Diode (LED). LED is a type of lighting that uses semiconductors to convert electricity into light. It is  usually  used  outdoors  as  a  sign  of  a  place  or  to  display advertisements.  The  purpose  of  this  research  is  to  analyze  the implementation of the videotron advertisement tax collection policy in order  to  increase  advertisement  tax  revenue  at  the  Regional  Tax Collection  Unit  of  Menteng,  Central  Jakarta  in  2021,  using  a qualitative method where primary data is obtained through interviews and  secondary  data.  The  results  of  this  analysis  explain  that  the implementation of the videotron advertisement tax collection policy in order  to  increase  advertisement  tax  revenue  at  the  Regional  Tax Collection Unit of Menteng, Central Jakarta in 2021 is categorized as good in terms of 4 (four) aspects,  namely : 1) Communication, 2) Resources, 3) Disposition, and 4) Bureaucratic Structure, with a slight problem in the Resources aspect where the ratio of tax officers is still very small compared to the number of videotron advertisement tax objects.